The Selective Antagonism of Adenosine A2B Receptors Reduces the Synaptic Failure and Neuronal Death Induced by Oxygen and Glucose Deprivation in Rat CA1 Hippocampus in Vitro - Fusco, Irene; Ugolini, Filippo; Lana, Daniele; Coppi, Elisabetta; Dettori, Ilaria; Gaviano, Lisa; Nosi, Daniele; Cherchi, Federica; Pedata, Felicita; Giovannini, Maria G.; Pugliese, Anna M. (Frontiers in Pharmacology, 2018)
Ischemia is a multifactorial pathology characterized by different events evolving in time. Immediately after the ischemic insult, primary brain damage is due to the massive increase of extracellular glutamate. Adenosine in the brain increases dramatically during ischemia in concentrations able to stimulate all its receptors, A1, A2A, A2B and A3. Although adenosine exerts clear neuroprotective effects through A1 receptors during ischemia, the use of selective A1 receptor agonists is hampered by their undesirable peripheral side effects. So far, no evidence is available on the involvement of adenosine A2B receptors in cerebral ischemia. This study explored the role of adenosine A2B receptors on synaptic and cellular responses during oxygen and glucose deprivation (OGD) in the CA1 region of rat hippocampus in vitro. We conducted extracellular recordings of CA1 field excitatory post-synaptic potentials (fEPSPs); the extent of damage on neurons and glia was assessed by immunohistochemistry. Seven min OGD induced anoxic depolarization (AD) in all hippocampal slices tested and completely abolished fEPSPs that did not recover after return to normoxic condition. Seven min OGD was applied in the presence of the selective adenosine A2B receptor antagonists MRS1754 (500 nM) or PSB603 (50 nM), separately administered 15 min before, during and 5 min after OGD. Both antagonists were able to prevent or delay the appearance of AD and to modify synaptic responses after OGD, allowing significant recovery of neurotransmission. Adenosine A2B receptor antagonism also counteracted the reduction of neuronal density in CA1 stratum pyramidale, decreased apoptosis at least up to 3 hours after the end of OGD, and maintained activated mTOR levels similar to those of controls, thus sparing neurons from the degenerative effects caused by the simil-ischemic conditions. Astrocytes significantly proliferated in CA1 stratum radiatum already 3 h after the end of OGD, possibly due to increased glutamate release. A2B receptor antagonism significantly prevented astrocyte modifications. Both A2B receptor antagonists did not protect CA1 neurons from the neurodegeneration induced by glutamate application, indicating that the antagonistic effect is upstream of glutamate release. The selective antagonists of the adenosine A2B receptor subtype may thus represent a new class of neuroprotective drugs in ischemia.